Recurrent infections in homozygous sickle cell disease. Issue 6 (1st June 1999) - Magnus, Stephen A; Hambleton, Ian R; Moosdeen, Faridah; Serjeant, Graham R
Abstract : The characteristics of 214 episodes of invasive bacterial infection among 176 patients with homozygous sickle cell (SS) disease were examined . Streptococcus pneumoniae occurred in 81 episodes, Salmonella spp in 70, Haemophilus influenzae type b in 30, Escherichia coli in 24, and Klebsiella spp in nine. The cumulative incidence showed that S pneumoniae and H influenzae occurred predominantly before 5 years of age and were uncommon thereafter, Salmonella spp increased almost linearly with age, and Klebsiella spp and E coli predominated in patients over 10 years of age. Escherichia coli had a different epidemiology—it was found in older children, almost entirely girls. Excluding this organism from an analysis of recurrent bacterial infections, the standardised incidence rates for second and third infections were 4.8 and 15.8 times greater, respectively, than the SS population average. This implies that the susceptibility to infection is characteristic of a subgroup of patients with SS disease and that sick patients with previous bacteraemia should be investigated early and aggressively for further infection.